2016
DOI: 10.1016/j.jvoice.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan in Human Vocal Folds in Smokers and Nonsmokers—A Histochemical Study

Abstract: Summary Objectives/hypothesisTo study the hyaluronan occurrence in human vocal folds, with special regards to gender and smoking and to discuss the implications of findings. Study DesignThis is a descriptive/morphologic study. MethodsSixteen cadaveric vocal folds from eight individuals between 58 and 90 years old (six women and two men) were removed and studied morphologically. Three of the individuals had been cigarette smokers.A direct method for hyaluronan histochemistry using a hyaluronan-binding protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The authors were blinded during evaluation. In the HA slides, staining intensity was scored in the epithelium, stroma and papilloma tissue using a modified grading scale by Opheim et al [10] designed to semiquantify the HA staining intensities with grading 0: no staining, 1: faint staining and 2: intense staining. In the CD44 slides, two parameters were evaluated for epithelium, stroma and RRP lesions respectively: The first was presence of CD44 (0: no stain, 1: visible staining) and the second congruence with HA staining (plus (þ): congruence, minus (À): no congruence).…”
Section: Histochemistry Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors were blinded during evaluation. In the HA slides, staining intensity was scored in the epithelium, stroma and papilloma tissue using a modified grading scale by Opheim et al [10] designed to semiquantify the HA staining intensities with grading 0: no staining, 1: faint staining and 2: intense staining. In the CD44 slides, two parameters were evaluated for epithelium, stroma and RRP lesions respectively: The first was presence of CD44 (0: no stain, 1: visible staining) and the second congruence with HA staining (plus (þ): congruence, minus (À): no congruence).…”
Section: Histochemistry Evaluationmentioning
confidence: 99%
“…In human VF, only a few reports on the occurrence and distribution of HA are available [4,10]. In these reports, materials and methods differ, the small sample sizes affect the reliability of the study outcome, and the findings have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 8 cadavers (6 female and 2 male, 3 smokers) found greater amounts of HA in the vocal folds of smokers than nonsmokers. However, this was performed by staining tissue samples, a method that does not quantify HA 20 . RE is characterized by increased tissue viscosity and volume, and both biomechanical properties are related to the presence of HA in the vocal folds 5 .…”
mentioning
confidence: 99%
“…However, this was performed by staining tissue samples, a method that does not quantify HA. 20 RE is characterized by increased tissue viscosity and volume, and both biomechanical properties are related to the presence of HA in the vocal folds. 5 Therefore, RE might be related to an increased concentration of the HA component of the extracellular matrix.…”
mentioning
confidence: 99%